An Energy‐Dense, Powerful, Robust Bipolar Zinc–Ferrocene Redox‐Flow Battery. Issue 30 (10th June 2022) - Luo, Jian; Hu, Bo; Hu, Maowei; Wu, Wenda; Liu, T. Leo
Abstract: Zinc metal represents a low‐cost, high‐capacity anode material to develop energy‐dense aqueous redox‐flow batteries (RFB). However, the energy‐storage applications of traditional inorganic Zn halide flow batteries are primarily plagued by the material challenges of traditional halide cathode electrolytes (e.g., bromine), including corrosion, toxicity, and severe crossover. Herein, we report a bipolar zinc–ferrocene salt compound, zinc 1, 1′‐bis(3‐sulfonatopropyl)ferrocene, Zn[Fc(SPr)2 ] (1.80 M solubility or 48.2 Ah L − charge storage capacity)—a robust, energy‐dense, bipolar redox‐active electrolyte material for RFBs. Zn[Fc(SPr)2 ] ‐based redox‐flow batteries operated at high current densities of up to 200 mA cm −2 and delivered an energy efficiency of up to 81.5 % and a power density of up to 270.5 mW cm −2 . A Zn[Fc(SPr)2 ] flow battery demonstrated an energy density of 20.2 Wh L −1 and displayed nearly 100 % capacity retention for 2000 cycles (1284 h or 53.5 days). Abstract : A robust redox‐flow battery is developed using a zinc–ferrocene bipolar electrolyte. This bipolar zinc–ferrocene redox‐flow battery outperforms all previously reported aqueous organic redox‐flow batteries (AORFBs) in terms of demonstrated energy density, power density, cycles and duration, and cycling stability.